2021
DOI: 10.1017/jrc.2021.2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of systematic reviews of secondary health conditions, health promotion, and employment of people with intellectual disabilities

Abstract: This is a systematic review of systematic reviews of secondary health conditions, health promotion interventions, and employment in people with intellectual disabilities. Articles were included if they reported a systematic review of health and employment, secondary health conditions, and health promotion interventions for people with intellectual disabilities. The methodological quality of the included reviews was reviewed using the A MeaSurement Tool to Assess systematic Reviews quality rating system, a meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Competitive integrated employment (CIE) is important for the health, psychological, and social well-being of individuals both with and without disabilities (Fryers, 2006;Iwanaga et al, 2021;Kamerāde et al, 2019;Taylor et al, 2022). In recent major rehabilitation legislation, the Workforce Innovation and Opportunity Act of 2014 (WIOA) and the Rehabilitation Act of 1973 as amended, CIE is the primary target goal for all persons with disabilities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Competitive integrated employment (CIE) is important for the health, psychological, and social well-being of individuals both with and without disabilities (Fryers, 2006;Iwanaga et al, 2021;Kamerāde et al, 2019;Taylor et al, 2022). In recent major rehabilitation legislation, the Workforce Innovation and Opportunity Act of 2014 (WIOA) and the Rehabilitation Act of 1973 as amended, CIE is the primary target goal for all persons with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, work provides a sense of belonging in a community and contributes to the satisfaction of doing things well (Taylor et al, 2022). CIE also contributes to higher self-esteem, which leads to a higher sense of self-worth and better mental health outcomes (Wehman et al, 2021). Additional benefits of being employed that are critical aspects of an individual's health and well-being include having a daily routine, having shared goals with coworkers, and contributing to a personal identity (Kamerāde et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In operationalising CIE as a public service outcome and the goal of policy, conceptualization has primarily been as an outcome in‐and‐of‐itself. However, research has also indicated that CIE may in turn provide other advantages and opportunities for individuals with disabilities; beyond serving as an outcome in and of itself, meaningful employment may provide economic opportunity (e.g., Taylor et al, 2021), better quality of life (e.g., Beyer et al, 2010; Dean et al, 2018; Iwanaga et al, 2021), and perhaps even better health outcomes (e.g., Inge et al, 2009; Robertson et al, 2019). These benefits of employment are not limited to individuals with intellectual and developmental disabilities; research examining the global population (with and without disabilities) has found substantial links between employment and happiness, quality‐of‐life, and other non‐monetary benefits (De Neve & Ward, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In operationalising CIE as a public service outcome and the goal of policy, conceptualization has primarily been as an outcome in-and-of-itself. However, research has also indicated that CIE may in turn provide other advantages and opportunities for individuals with disabilities; beyond serving as an outcome in and of itself, meaningful employment may provide economic opportunity (e.g., Taylor et al, 2021), better quality of life (e.g., Beyer et al, 2010;Dean et al, 2018;Iwanaga et al, 2021), and perhaps even better health outcomes (e.g., Inge et al, 2009;Robertson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%